Successful talent development environments in female Scandinavian handball: Constellations of communities of practice and their implications for role modeling and interactions between talents, senior players and coaches - Kamuk Storm, L.; Krogh Christensen, M.; Ronglan, L. T. (Scandinavian Journal of Sport and Exercise Psychology, 2020)
Talent development is a sociocultural affair. The social learning perspective is rarely used for the study of talent development in sport, although it is broadly known in the domain of education. This article examines the way in which communities of practice are connected within two successful handball clubs, what characterises talents` movements across communities of practice within the club, and what characterises the interactions between talents, senior players and coaches. Drawing on Wenger`s notion of communities of practice, constellations of interconnected practices and boundary encounters, it identifies how the two environments were characterised by (1) a wellfunctioning constellation of several CoPs, (2) opportunities for talents to participate and engage in various CoPs (3), individually adjusted feedback from coach to player combined with communication between the players with different positions in the CoPs and not only coach instructions, and (4) senior elite players` engaging behaviours in regard to newcomers in the boundary encounters and thereby legitimate peripheral participation opportunities for talented players. (5) The coaches were the key to coordinate the interconnected practices and social interactions between the `youth CoP` and `senior elite CoP`.